K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

14 tháng 10 2015

(x-5).(x-7)=0

=> x-5=0  hoặc   x-7=0

=> x= 5 hoặc x=7 

Vậy x=5 ; 7

3 tháng 7 2017

(x-5)(x-7)=0

th1: x-5=0

      x=5

th2: x-7=0

     x=7

3 tháng 7 2017

X=5 hoặc 7 nha chỉ cần lắp vào thui

6 tháng 2 2021

a) \(15-5\left|x+4\right|=-12-3\)

\(\Leftrightarrow5\left|x+4\right|=30\)

\(\Leftrightarrow\left|x+4\right|=6\)

\(\Leftrightarrow\orbr{\begin{cases}x+4=6\\x+4=-6\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2\\x=-10\end{cases}}\)

b) \(\left(4x-8\right)\left(7-x\right)=0\Leftrightarrow\orbr{\begin{cases}4x-8=0\\7-x=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2\\x=7\end{cases}}\)

c) \(\left(x^2-36\right)\left(x^2+5\right)=0\Rightarrow\left(x-6\right)\left(x+6\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x-6=0\\x+6=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=6\\x=-6\end{cases}}\)

d) \(-3\left(x+7\right)-11=2\left(x+5\right)\)

\(\Leftrightarrow-3x-32=2x+10\)

\(\Leftrightarrow5x=-42\Rightarrow x=-\frac{42}{5}\)

5 tháng 8 2018

(82 - 5.x) : 13 - 4 = 0

(82 - 5.x) : 13 = 0 + 4

(82 - 5.x) : 13 = 4

(82 - 5.x) = 4 . 13

(82 - 5.x) = 52

5.x  = 82 - 52

5.x = 30

x = 30 : 5 = 6

(32 . 45) : 2 = (x + 70) : 14 - 40

720 = (x + 70) : 14 - 40

(x + 70) : 14 = 720 + 40

(x + 70) : 14 = 760

(x + 70) = 760 . 14

(x + 70) = 10640

x = 10640 - 70

x = 10570

5 tháng 8 2018

Tìm x biết : 

( 82 - 5 . x ) : 13 - 4 = 0 

( 82 - 5 . x ) : 13 = 0 + 4 

( 82 - 5 . x )  : 13 = 4 

82 - 5 . x = 4 × 13 

82 - 5 . x = 52 

5 . x = 82 - 52 

5 . x = 30 

x = 30 : 5 

x = 6

Vậy x = 6

17 tháng 8 2016

=>\(\left(\frac{49}{9}+x-\frac{133}{18}\right):\frac{108}{7}=1\)

=>\(\frac{49}{9}+x-\frac{133}{18}=\frac{108}{7}\)

=>\(\frac{49}{9}+x=\frac{108}{7}+\frac{133}{18}\)

=>\(\frac{49}{9}+x=\frac{2875}{126}\)

=>\(x=\frac{2975}{126}-\frac{49}{9}\)

=>\(x=\frac{2189}{126}\)

22 tháng 9 2020

2189/162

nhớ đưa 100000000000000000000000000000000000000000000000000000000k ok

15 tháng 5 2015

\(\frac{x-1}{5}+\frac{x-1}{7}+...+\frac{x-1}{37}=0=>\left(x-1\right).\left(\frac{1}{5}+\frac{1}{7}+...+\frac{1}{37}\right)=0\)

mà \(\frac{1}{5}+\frac{1}{7}+...+\frac{1}{37}>0\)

=> x-1 = 0

=> x = 1

Vậy x=1

đúng nha

AH
Akai Haruma
Giáo viên
6 tháng 7 2024

Lời giải:

$x-\frac{1}{3}+x-\frac{1}{5}+x-\frac{1}{7}+x-\frac{1}{9}=0$

$(x+x+x+x)-(\frac{1}{3}+\\frac{1}{5}+\frac{1}{7}+\frac{1}{9})=0$

$4\times x-\frac{248}{315}=0$

$4x=\frac{248}{315}$

$x=\frac{248}{315}:4=\frac{62}{315}$